Sleep duration of lactating mothers and its relationship with feeding pattern, milk macronutrients and related serum factors: A combined longitudinal cohort and cross-sectional study - Huijuan Ruan; Yajie Zhang; Yajie Zhang; Qingya Tang; Xuan Zhao; Xuelin Zhao; Yi Xiang; Wei Geng; Yi Feng; Wei Cai; Wei Cai; Wei Cai (Frontiers in Nutrition, 2022)
ObjectiveInsufficient sleep is common in postpartum mothers. The main objectives of this study are to explore the sleep duration among Chinese lactating mothers and preliminarily investigate the relationship between sleep duration and feeding pattern. The secondary objectives are to investigate the relationships between sleep duration and milk macronutrients and between maternal-related indicators, including melatonin (MT), growth hormone (GH), ghrelin (GHRL), glucagon-like peptide-1 (GLP-1), prolactin (PRL), and cholecystokinin (CCK).MethodsThe present study comprises a longitudinal and a cross-sectional cohort from December 2019 to December 2021. Postpartum lactating women living in Shanghai were recruited through online and offline recruitment. The subjects were included in the longitudinal cohort or cross-sectional study based on their lactation period at the time of recruitment. The longitudinal cohort included a total of 115 mothers. Human milk and feeding pattern were measured and collected at 2–4 months and 5–7 months postpartum. At four predetermined follow-up time points, data on sleep duration was collected (at the time of recruitment, 2–4 months postpartum, 5–7 months postpartum, and 12–17 months postpartum). The cross-sectional study included 35 lactating mothers (2–12 months postpartum) who reported their sleep duration and provided blood samples. Mid-infrared spectroscopy (MIRS) method was used to analyze the macronutrients of breast milk, while MT, GH, GHRL, GLP-1, PRL, and CCK in maternal blood were determined by ELISA.ResultsThe maternal sleep duration before pregnancy was 8.14 ± 1.18 h/d (n = 115), 7.27 ± 1.31 h/d (n = 113) for 2–4 months postpartum, 7.02 ± 1.05 h/d (n = 105) for 5–7 months postpartum, and 7.45 ± 1.05 h/d (n = 115) for 12–17 months postpartum. The incidence of insufficient sleep (<7 h/d) before pregnancy (12.17%) was significantly less than at any follow-up time after delivery (vs. 2–4 months postpartum, χ2 = 10.101, p = 0.001; vs. 5–7 months postpartum, χ2 = 15.281, p < 0.0001; vs. 12–17 months postpartum, χ2 = 6.426, p = 0.011). The percentage of insufficient maternal sleep was highest at 5–7 months postpartum (34.29%). No significant difference was found between the incidence of insufficient sleep at 5–7 months postpartum, 2–4 months postpartum (29.20%, χ2 = 0.650, p = 0.420), and 12–17 months postpartum (25.22%, χ2 = 2.168, p = 0.141). At 2–4 months postpartum, the frequency of formula feeding per day is related to reduced maternal sleep duration (Standardization coefficient β = −0.265, p = 0.005, Adjusted R2 = 0.061). At 2–4 months and 5–7 months postpartum, the relationship between macronutrients in breast milk and the mother's sleep duration was insignificant (all p > 0.05). Other than the positive correlation found between maternal GHRL and sleep duration (r = 0.3661, p = 0.0305), no significant relationship was observed between sleep duration and other indexes (all p > 0.05).ConclusionsPostpartum mothers generally sleep less, but there is no correlation between insufficient sleep and the macronutrient content of breast milk. Formula feeding may be related to the mother's sleep loss, while breastfeeding (especially direct breastfeeding) may be related to increased maternal sleep duration. The findings suggest that sleep duration is related to maternal serum GHRL. More high-quality studies are needed to clarify the mechanism of these findings and provide a solid theoretical basis and support references for breastfeeding.